2021
DOI: 10.1038/s41598-021-98762-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability, reproducibility, and agreement of three tonometers for measuring intraocular pressure in rabbits

Abstract: The aim of this study was to evaluate repeatability, reproducibility, and agreement of three commonly used tonometers in animal research (TonoLab, TonoVet, and TonoPEN AVIA) in a cohort of 24 rabbits. Additionally, the impact of sedation on IOP was investigated in 21 New Zealand White rabbits with the TonoVet tonometer. Repeatability was determined using the coefficient of variation (CoV) for two observers. For the TonoLab (6.55%) and TonoVet (6.38%) the CoV was lower than for the TonoPEN AVIA (10.88%). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…IOP deviations are often small within this type of animal model, as normotensive animals without glaucoma are used. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…IOP deviations are often small within this type of animal model, as normotensive animals without glaucoma are used. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Acquiring intraocular pressures (IOP) by tonometry is an important part of comprehensive ophthalmic examination in a research setting. Prior studies have investigated the use of various tonometers such as the TonoVet, Tonolab, TonoVet Plus, Perkins applanation tonometer, TonoPen Avia, TonoPen, TonoPen XL, and TAO1 in rabbits both in vivo and ex vivo 4–11 . The Reichert Tono‐Vera® Vet is a tonometer that was released for commercial use in January 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have investigated the use of various tonometers such as the TonoVet, Tonolab, TonoVet Plus, Perkins applanation tonometer, TonoPen Avia, TonoPen, TonoPen XL, and TAO1 in rabbits both in vivo and ex vivo. [4][5][6][7][8][9][10][11] The Reichert Tono-Vera® Vet is a tonometer that was released for commercial use in January 2021. This rebound tonometer has four different species-specific settings for dogs, cats, horses, and rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…6 Research comparing various models of tonometers has shown that different IOP values are obtained depending on the equipment used. [7][8][9][10][11] Although reference values for tear production and IPO have been described for some breeds of rabbits in numerous scientific articles, the results vary greatly. Normal values for tear production have been described in New Zealand, [12][13][14] English Angora, and Mini Holstein 15 rabbits.…”
mentioning
confidence: 99%
“…Likewise, IOP reference values and comparisons between values obtained by different tonometers were established for New Zealand and Dutch Belted rabbits. 10,11,[16][17][18][19][20][21] With the growing popularity of pet rabbits, the determination of basic ophthalmic parameters becomes essential, since the physiological parameters of a given species or breed are fundamental for the diagnosis and monitoring of their ocular diseases. 6,22 This determination becomes even more important in rabbits, which have a circadian rhythm that is different from other species of domestic animals and show different IOP throughout the day.…”
mentioning
confidence: 99%